2010
DOI: 10.1123/pes.22.1.93
|View full text |Cite
|
Sign up to set email alerts
|

Paraoxonase Activity in Athletic Adolescents

Abstract: Regular physical activity may play a protective role against cardiovascular disease in adults, and paraoxonase activity may serve to mediate this effect. This study compared paraoxonase activity and that of other antioxidative agents in adolescent athletes compared with inactive youth. Paraoxonase level was 177.32 +/- 100.10 (U/L) in children with regular physical activity and 98.11 +/- 40.92 (U/L) in the control group (P < 0.0001). The levels of total antioxidative capacity, total oxidative status, oxidative … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
19
0
3

Year Published

2011
2011
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(24 citation statements)
references
References 55 publications
2
19
0
3
Order By: Relevance
“…Cakmak A. et al 52) found that PON1 activities, were significantly higher in trained adolescent athletes than in controls. PON1 activities were remarkably higher in adolescents involved in wrestling (which is anaerobic in nature) at baseline than in those who were sedentary.…”
Section: Training Effects On Blood Tdpon1 Activities and Pon1p Involvmentioning
confidence: 99%
“…Cakmak A. et al 52) found that PON1 activities, were significantly higher in trained adolescent athletes than in controls. PON1 activities were remarkably higher in adolescents involved in wrestling (which is anaerobic in nature) at baseline than in those who were sedentary.…”
Section: Training Effects On Blood Tdpon1 Activities and Pon1p Involvmentioning
confidence: 99%
“…Hamurcu et al 14 demonstrated higher serum PON1 activity in wrestlers than sedentary. Cakmak et al 15 found higher serum PON1 activity athletic adolescents with regular physical activity than in controls. On the other hand, a previous study reported significantly increased PON1 activity values in well-trained rugby players compared with sedentary controls 32 .…”
Section: Discussionmentioning
confidence: 99%
“…In addition, oxidative stress has been reported to affect the expression and activity of PON1 8,9 . Several studies have investigated PON1 activity in many different conditions 3,14,15 . Tomas et al 3 assessed the effects of a single bout of exercise on PON1 activity in humans.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been demonstrated that the plasma PON1 activity is elevated in athletic adolescents who engage in regular physical activity, and in football players three days after a tournament [7,15]. In addition, five months of anaerobic training induced an elevation in the circulating PON1 activity [83].…”
Section: Paraoxonase 1 Myeloperoxidase and Physical Activitymentioning
confidence: 99%